Quantification of the Impact of Big Five Personality Traits on Political Skills - Dubey, Akanksha; Pandey, Mrinalini (Prabandhan: Indian Journal of Management, 2017)
This paper investigated the impact of different personality traits on political skills in an individual. Here, Big Five traits of personality were considered. A self rated questionnaire was used to determine the effect on political skills due to Openness, Conscientiousness, Extrovert, Agreeableness, and Emotional Stability, respectively. Three hundred and eighteen (318) participants provided responses for measures of the five factor model and political skills. Multiple regression tool was applied to find the impact of personality traits. The results showed that Conscientiousness had the highest impact on individual's political skills, while Openness had the least impact on political skills. Individuals working in an institute can make good use of this as they will be able to gauge political skills of their colleagues on the basis of their respective personality types.